The influence of higher surface hardness on fretting fatigue life of hard anodized aerospace AL7075-T6 alloy - Sarhan, Ahmed Aly Diaa Mohammed; Zalnezhad, E.; Hamdi, M. (Elsevier, 2012)
In this research work, the influence of higher surface hardness on the fretting fatigue life of hard anodized aerospace AL7075-T6 alloy was investigated. An optimization of the parameters of hard anodized Al7075-T6 alloy to obtain higher surface hardness was presented. Confirmation test was carried out to show the improvement after using the best parameter combination attained from the optimization process. The result shows that hard anodized coating (surface with hardness of 360 HV and thickness of around 17 Î¼m) can significantly improve fretting fatigue life of specimens at low stress, while at high stress, the extent of fretting fatigue life decreases. Hard anodized coating with higher thickness (29 mm) and high surface hardness (393 HV) decreased the fretting fatigue life of specimens at stresses beyond 200 MPa, this mainly attributed to the coating brittleness and micro-cracking.